Pemikiran Abed Al-Jabiri Terhadap Nalar Arab: Konsep dan Relevansi - Yandi Hafizallah; Muhammad Abdul Wafa (Mawaizh : Jurnal Dakwah dan Pengembangan Sosial Kemanusiaan, 2019)
This paper aims to explain and analyze the epistemological aspects based on the thoughts of Abed al-Jabiri, especially regarding the thinking of three Arabic reasoning of al-Jabiri. The study refers to three thoughts of Arabic al-Jabiri reasoning about epistemology namely: "epistemology of Bayani", the epistemology of Irfani ", and" epistemology of Burhani". The search for the texts relating to the three epistemologies produces several findings in this study, among others: 1) Relevance between three Arabic reasoning that does not always stand alone but all three reasoning are also integrated with each other, even though Arabic reasoning is a formation from a culture; 2) The shift of reasoning culture analyzed using the socio-historical approach to the development of Arabic reasoning makes Jabiri make Arabic reasoning a "thinking structure", each of which has advantages and disadvantages; 3) The criticisms of the reasoning model conducted by Abed al-Jabiri are used to formulate methods of understanding knowledge. The three Arabic reasonings described by abed al-Jabiri rely on aspects emphasized in reason and reality, philosophy and science, and revelation texts and Nash.